Contact injuries in field hockey and the potential role for personal protective equipment - Rees, H.; McCarthy Persson, U.; Delahunt, E.; Boreham, C.; Blake, C. (Journal of Sports Sciences, 2023)
Field hockey is played with sticks and a hard ball. It is fast-paced, with athletes playing together in close proximity. Athletes may be at increased risk of sustaining injuries through contact. The aim of this study was to investigate the epidemiological characteristics of contact injuries in field hockey. Data were collected during the 2017/2018 and 2018/2019 Irish Hockey League seasons. This study included two methods of data collection among male athletes: self-reported injuries and via those reported by the teams` physiotherapists. Injuries were defined as any physical complaint sustained during field hockey, supplemented by medical attention and time-loss injuries. Only contact injuries were included for analysis. Overall, 107 contact injuries were incurred, giving rise to an injury incidence rate of 3.1/1000 h, and accounting for 33.1% of all injuries. Athletes had an absolute risk of 0.372 of sustaining a contact injury. Contusions (48.6%) were the most common type of contact injury, while injuries to the head/face (20.6%) were the most frequently reported location. Contact injuries represent an important proportion of all injuries. Rule changes to mandate the use of personal protective equipment in field hockey may assist in reducing the absolute risk and severity of contact injuries in field hockey.